2016
DOI: 10.1007/978-3-319-43350-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Towards Inclusive Water Governance: OECD Evidence and Key Principles of Stakeholder Engagement in the Water Sector

Abstract: Citizens increasingly demand to be more engaged in how public policy decisions are made. In this environment, stakeholder engagement has emerged as a principle of good water governance. However, despite extensive research and case studies on the topic in recent years, the lack of evidence-based assessment on how effective engagement processes have proven to be in reaching intended objectives of water governance is striking. Most participatory evaluation exercises fail to provide decision-makers with the eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Formalised governance spaces have the potential to promote strong legitimacy, better-informed stakeholders, confident, committed, and skilled staff, and stakeholders [ 61 ]. Our review identified significant policy/implementation gaps, demonstrating that community participation is not just about creating structures but functionally and sustainably transferring power and authority to marginalized people.…”
Section: Discussionmentioning
confidence: 99%
“…Formalised governance spaces have the potential to promote strong legitimacy, better-informed stakeholders, confident, committed, and skilled staff, and stakeholders [ 61 ]. Our review identified significant policy/implementation gaps, demonstrating that community participation is not just about creating structures but functionally and sustainably transferring power and authority to marginalized people.…”
Section: Discussionmentioning
confidence: 99%
“…Successful community engagement in watershed management requires a process that brings together stakeholders, including government agencies, non-profit organizations, and community groups [160,167]. Community participation can include various activities, such as education and training, citizen science, and volunteering, and can take the form of public meetings, seminars, and outreach initiatives.…”
Section: Community Engagementmentioning
confidence: 99%
“…Likewise, recent literature on energy transition often concentrates on the role of local and civic actors, and scholars widely agree that, among other factors, their inclusion is a central aspect in the transition to renewable energy [37,38]. Nabiafjadi et al [39], who conducted an empirical network analysis in the Middle East about water governance, emphasized the need to decentralize administration to local, private, or non-governmental actors in order to improve water governance [40]. Hegga et al went one step further, examining what actual capacities local actors-who seem to be already integrated into the implementation of policies through decentralization in water services-need in order to successfully participate in the operation and management of water services [41].…”
Section: Local Actors In a Multi-level Perspectivementioning
confidence: 99%